Monitoring faecal contamination and relationship of physicochemical variables with faecal indicator bacteria numbers in Bukavu surface waters, tributaries of Lake Kivu in Democratic Republic of Congo - Arthur Mubwebwe Bisimwa; Bramuel Kisuya; Zoé Malumba Kazadi; Bamba Bukengu Muhaya; Alidor Busanga Kankonda (Elsevier, 2022)
The faecal indicator bacteria (FIB) in association with physicochemical parameters were monitored twice a month from 2017 to 2019 in the Kahuwa (KW), Wesha (WS), Tshula (TL), Bwindi (BN), and Nyamuhiga (NG) rivers and their tributaries. Results showed severe faecal contamination of waters compared to the WHO standards, and the FIB load levels (Mesophilic aerobic bacteria (MAB), Total coliforms (TC), Faecal coliforms (FC), and Faecal streptococci (FS)) were varied between stations (Kruskal-Wallis test (K) = 703; p < 0.01) and seasons (Fisher's test (F) = 2.13; p < 0.01). However, the presence of pathogenic bacteria such as Escherichia coli, Salmonella typhi, Streptococcus sp., Shigella dysenteriae, Aeromonas sp., Vibrio cholerae, and other bacteria indicative of faecal contamination were reported. Water temperature (WT) and dissolved oxygen (DO) were within the WHO standards for surface waters, except pH for some stations on KW and NG rivers, where it was highly alkaline. The highest nutrients concentrations (PO43-, NH4+, NO2- and NO3-) were recorded in the dry season for all stations, except in KW and NG rivers from the midstream to downstream stations. The structural equations regression model (F test, p ≤ 0.05 with R2) indicated a significant (p ≤ 0.05) positive correlation between the value of physicochemical parameters (WT, pH, PO43-, NH4+, NO2- and NO3-) and that of detected FIB numbers, except for DO which negatively affects bacteria numbers. The FC/FS ratio (1.01 - 4.30) linked polluted waters to human sources while the COD/BOD5 ratio (1.90 - 2.39) categorized them under domestic origin wastewater. The current degradation status of these rivers require a rapid waste management strategy and an efficient sanitation plan development along each catchment. Installation of wastewater treatment plants (WWTPs) with biological treatment can mitigate the ecological and health risks of the rivers and the coastal zone of Lake Kivu.